Evaluación del impacto ambiental del hospital militar básico 17 - bs de la ciudad de puyo, aplicando las normas mexicanas (nmx - aa - 015, 019, 022 - 1985), para proponer un plan de manejo ambiental - Zurita Meneces, Verónica Jeanneth (2016)
The problem that was identified to carry out the investigative work is the environmental impact caused by the Basic Military Hospital Nº17-bs from the Puyo City, which generates large amounts of wastes harmful to the environment and that at the mere perception aren`t handled properly. Through an investigation made in the hospital, an evaluation was carried out on the environmental impacts, the management of wastes generated by the hospital and the characterization of the same, for which an environmental management plan was proposed in the Basic Military Hospital Nº17-bs, was used different methods such as surveys, sampling and data collection, for this the Mexican norms were applied (NMX-AA-15, 019, 022 - 1985), to get the expected results of this research. Over the work made of the characterization in the hospital during the week, the amount of 111,5 kg/w, with a per-capita average of 0,22 kg/person/day, was obtained, after that was performed with the quartering C and D, showing results of the amount of 60,80 kg/w, giving the volumetric weight average of 736,43 kg / mᵌ. With the results of the research will be of vital importance for the creation of the environmental management plan at the Basic Military Hospital Nº17-BS, with programs to improve the proper management of wastes, training and education in the environmental and safety area, to carry out the respective monitoring and follow-up, programs that must be socialized and executed jointly with the authorities, employees and workers of the Basic Military Hospital Nº 17-BS.